Kakuriyo, bed & breakfast for spirits. 9 - Yuma, Midori; Ioka, Waco; Kimura, Tomo (Shojo beat manga., 2024)
"Aoi is getting ready to launch a summer shaved ice campaign at her restaurant when a trio of children staying at the inn goes missing. Even though she's not technically an employee, Aoi isn't going to sit around when kids might be in trouble. She joins Akatsuki in his search of the tunnels under Tenjin-ya and finds more than she was looking for when she stumbles into a dusty subterranean room full of mysterious portraits from the Ōdanna's past"--Provided by publisher.